2016
DOI: 10.21548/34-1-1084
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Extended Grape Ripening With or Without Must and Wine Alcohol Manipulations on Cabernet Sauvignon Wine Sensory Characteristics

Abstract: This study attempts to clarify the consequences for wine flavour that result from harvesting fruit at different maturities. The grapes were harvested from a single vineyard in Paso Robles, and the samples spanned maturity levels from what would be considered early harvest (about 21 °Brix) to late harvest (about 30 °Brix). The wines made from these grapes were analysed using descriptive analysis to investigate the relationships between fruit maturity and wine sensory attributes. In addition, musts and/or wines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 34 publications
0
24
0
Order By: Relevance
“…As expected, taste attributes were relatively simple to define and explain in relation to certain aspects of wine composition. Regarding palate sensation attributes, a clear relationship between 'hotness' and ethanol concentration was observed (R = 0.84), as documented in studies incorporating progressive grape ripening (Heymann et al 2013, Bindon et al 2014, Li et al 2017. Lack of clear relationship between 'acidity' and pH/TA is potentially linked to fluctuations due to acid adjustment and alterations during stabilisation, whereas further analysis of other aspects of wine composition, for example polysaccharides, might give more insight into the 'bitterness' perception (Mercurio and Smith 2008).…”
Section: Effects Of Non-volatile and Volatile Compounds On Wine Sensomentioning
confidence: 84%
See 1 more Smart Citation
“…As expected, taste attributes were relatively simple to define and explain in relation to certain aspects of wine composition. Regarding palate sensation attributes, a clear relationship between 'hotness' and ethanol concentration was observed (R = 0.84), as documented in studies incorporating progressive grape ripening (Heymann et al 2013, Bindon et al 2014, Li et al 2017. Lack of clear relationship between 'acidity' and pH/TA is potentially linked to fluctuations due to acid adjustment and alterations during stabilisation, whereas further analysis of other aspects of wine composition, for example polysaccharides, might give more insight into the 'bitterness' perception (Mercurio and Smith 2008).…”
Section: Effects Of Non-volatile and Volatile Compounds On Wine Sensomentioning
confidence: 84%
“…Lack of clear relationship between 'acidity' and pH/TA is potentially linked to fluctuations due to acid adjustment and alterations during stabilisation, whereas further analysis of other aspects of wine composition, for example polysaccharides, might give more insight into the 'bitterness' perception (Mercurio and Smith 2008). Regarding palate sensation attributes, a clear relationship between 'hotness' and ethanol concentration was observed (R = 0.84), as documented in studies incorporating progressive grape ripening (Heymann et al 2013, Bindon et al 2014, Li et al 2017. Increasing residual sugar, ethanol and tannin concentration were positively associated with 'palate fullness', whereas both 'astringency' and 'palate coarseness' were positively correlated with tannin concentration.…”
Section: Effects Of Non-volatile and Volatile Compounds On Wine Sensomentioning
confidence: 95%
“…Interactions between ethanol and astringency perception have also been found (Smith et al 1996). Heymann et al (2013) found that the method of ethanol adjustment was important, with fortified wines being rated sweeter, more bitter, astringent, hot, and viscous than unadjusted and chaptalized wines; however, fortification is not an accepted winemaking practice in table wine production. Overall, most studies investigating the sensory impact of wine ethanol concentrations found that perceived fruity characters were depressed in high alcohol wines, hot and viscous mouthfeel perceptions were enhanced, and sweet and bitter ratings were increased.…”
mentioning
confidence: 95%
“…Some information can be obtained from studies that have investigated harvest timing, and how this affects wine composition and/or sensory properties. Extended fruit maturation up to 30°Brix in California Cabernet Sauvignon was shown to increase the scores of some sensory properties, such as hotness, bitterness, sweetness and dark fruit (Heymann et al ). Wines produced from grapes sampled at low TSS had a higher score for sour and vegetative attributes (Heymann et al ).…”
Section: Introductionmentioning
confidence: 99%